Pengaruh Pengendalian Integrated Port Time (IPT) terhadap Kelancaran Kegiatan Bongkar Muat Di PT. Pertamina (Persero) Regional IV Semarang - Retno Indriyati; Barokhah Ardian (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2021)
This study aims to know the control pengaruruh Integrated Port Time (IPT) system on the smooth running of loading and unloading activities at PT. Pertamina (Persero) Regional IV Semarang. The author made observations at PT. Pertamina (Persero) Regional IV Semarang, besides that, also conducted interviews with people related to the problems discussed precisely in the Marine Function where there were several things that became problems in running the Integrated Port Time system, namely the high waiting time at the Port which had implications for costs. transportation, the length of time the ship at the terminal is influenced by many factors involving the functions of the Refinery Unit, S&D, Domas and Aviation and Shipping. In addition, the inadequate constraints on land and ship infrastructure have resulted in hampered operations. The author also collects literature from books, regulations and research related to integrated port time and loading and unloading. The results of the discussion show that there is an effect of integrated port time on the smooth loading and unloading process at PT. Pertamina (Persero) Regional IV Semarang. This can be proven by the high waiting time at the port which is one of the obstacles to the Integrated Port Time (IPT), this is due to the Waiting Time, Terminal Time, Lab Time Score, Marine Time and Finance Ops Time, the length of time the ship is at the terminal. resulting in delayed fuel distribution operations and inadequate ship and land infrastructure.